Solutan echinoderms from the Fezouata Shale Lagerstätte (Lower Ordovician, Morocco): diversity, exceptional preservation, and palaeoecological implications - Dupichaud, Christophe; Lefebvre, Bertrand; Milne, Claire H.; Mooi, Rich; Nohejlová, Martina; Roch, Renaud; Saleh, Farid; Zamora, Samuel (Frontiers in Ecology and Evolution, 2023)
In the Lower Ordovician of Morocco, solutan echinoderms are relatively common, locally abundant, geographically widespread (Central and Eastern Anti-Atlas), and biostratigraphically long-ranging (late Tremadocian-mid Floian) components of the Fezouata Biota. The lower part of the Fezouata Shale (late Tremadocian) yielded one specimen, here tentatively identified as a Castericystislike syringocrinid, with exceptionally preserved internal soft parts presumably corresponding to the distal region of the gut. Most solutan remains from the Fezouata Shale are assigned to Plasiacystis mobilis, which was already known from the late Tremadocian of France, and the Darriwilian of the Czech Republic and United Kingdom. Several isolated dististeles provisionally identified as Plasiacystis sp. may belong to large individuals of P. mobilis or to a new taxon. Several specimens of late Tremadocian solutans from the Fezouata Shale, morphologically intermediate between Minervaecystis vidali (late Tremadocian, France) and Plasiacystis mobilis, are assigned to Nimchacystis agterbosi gen. et sp. nov. The diagnosis of the syringocrinid family Minervaecystidae is modified to include the four genera Minervaecystis, Nimchacystis, Pahvanticystis, and Plasiacystis, all characterized by an ovoid theca, a laterally inserted feeding appendage, and a twisted, flattened dististele. Minervaecystids are interpreted as active epibenthic detritus feeders, using their dististele to crawl on soft substrates. The newly described solutan taxa highlight that the benthic communities of Fezouata Biota are more diverse than what was previously described.